War and Everyday life: Iran and America A Media Case Study - Amin Parvin; Seyed Abdolamir Nabavi (Taḥqīqāt-i Farhangī-i Īrān)
These days war has became one of the most important identical factors of the Middle East in western media. As war is representing the Middle East ugly and horrible to the public opinion, is being repeated normally in the lives of the Middle Eastern residents. On the other hand, the anti-war movements blame politicians and the terrorist groups. This article will consider such subject by emphasizing war as an everyday life issue in the Middle East (as multidimensional and culture phenomenon) and antiwar especially in America. The hypothesis is that war as a totality has covered all aspects of the Middle East residents (such as Iran) as has turned to part of their everyday life. On the contrary, anti-war in the western countries (America) has the same situation as above. In this paper, as a theoretical base, Zimmle, Marx, Weber, Lukach, Do serto, Foucault, Hall and Fisk will be used. The data has been collected in 1387 [2008] via qualitative methods (dialogue, observation and news analysis).